Biophysical and Structural Characterization of the Recombinant Human eIF3L - Morais, Ana T. S. [UNESP]; Meza, Andreia N.; Araujo, Gabriela C. [UNESP]; Vidotto, Alessandra; Souza, Fatima P. [UNESP]; Fossey, Marcelo A. [UNESP]; Murakami, Mario T.; Nogueira, Mauricio L. (Bentham Science Publ Ltd, 2014)
The eukaryotic translation initiation factor 3, subunit L (eIF3L) is one of the subunits of the eIF3 complex, an accessory protein of the Polymerase I enzyme and may have an important role in the Flavivirus replication by interaction with a viral non-structural 5 protein. Considering the importance of eIF3L in a diversity of cellular functions, we have produced the recombinant full-length eIF3L protein in Escherichia coli and performed spectroscopic and in silico analyses to gain insights into its hydrodynamic behavior and structure. Dynamic light scattering showed that eIF3L behaves as monomer when it is not interacting with other molecular partners. Circular dichroism experiments showed a typical spectrum of alpha-helical protein for eIF3L, which is supported by sequence-based predictions of secondary structure and the 3D in silico model. The molecular docking with the K subunit of the eIF3 complex revealed a strong interaction. It was also predicted several potential interaction sites in eIF3L, indicating that the protein is likely capable of interacting with other molecules as experimentally shown in other functional studies. Moreover, bioinformatics analyses showed approximately 8 putative phosphorylation sites and one possible N-glycosylation site, suggesting its regulation by post-translational modifications. The production of the eIF3L protein in E. coli and structural information gained in this study can be instrumental for target-based drug design and inhibitors against Flavivirus replication and to shed light on the molecular mechanisms involved in the eukaryotic translation initiation.
Keywords: Circular dichroism; Dynamic light scattering; eukaryotic translation initiation factor 3; subunit L; Molecular modeling